Superior energy storage capacity of polymer-based bilayer composites by introducing 2D ferroelectric micro-sheets - Zhenhao Fan; Jian Dai; Yuyan Huang; Hang Xie; Yitao Jiao; Wenfeng Yue; Fu Huang; Yuqun Deng; Dawei Wang; Qingfeng Zhang; Yunfei Chang (Nature Communications)
Abstract Dielectric polymer capacitors suffer from low discharged energy density and efficiency due to their low breakdown strength, small dielectric constant and large electric hysteresis. Herein, a synergistic enhancement strategy is proposed to significantly increase both breakdown strength and dielectric constant while suppressing hysteresis, through introducing 2-dimensional bismuth layer-structured Na0.5Bi4.5Ti4O15 micro-sheets and designing a unique bilayer structure. Excitingly, an ultra-high discharged energy density of 25.0 J cm−3 and a large efficiency of 81.2% are achieved in Na0.5Bi4.5Ti4O15-poly(vinylidene fluoride-co-hexafluoropropylene)/Na0.5Bi4.5Ti4O15-polyetherimide bilayer composites under a dramatically enhanced breakdown strength of 8283 kV cm−1. Finite element simulations along with experimental test results demonstrate that greatly improved breakdown strength is ascribed to uniform and horizontal alignments of Na0.5Bi4.5Ti4O15 sheets (~1–2 μm) in the matrix and interface effect of adjacent layers with large dielectric differences, which effectively inhibit electrical tree evolution and conduction loss. This work provides a strong foundation for developing high-performance polymer-based energy storage devices.